An electrocatalyst for detection of glucose in human blood: synergy in Pd–AuNPs/GOx/C surfaces. Issue 12 (2nd December 2019) - Celik Kazici, Hilal; Yayla, Muge
Abstract: Glucose oxidase (GOx)-based amperometric enzyme electrodes have been the target of substantial research. In this study, new amperometric biosensor for determination of glucose was developed. GOx enzyme was immobilized at bovine serum albumin via entrapment method. For this reason, the optimum conditions of Pd–Au NPs/GOx/C-modified glassy carbon electrode were determined. The electron is directly transferred from glucose to the electrode via the active site of the enzyme. The absence of mediators is the main advantage of such third-generation biosensors. The resulting materials were characterized employing scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction. In addition, the effects of glucose concentration, scan rate, temperature, electroactive interference, stability, reusability of the biosensors were discussed. The applicability to blood analysis was also evaluated. The biosensor has a limit of detection for the determination of glucose 0.0014 mM.